Small Comforts - Skelly, Priya (Tufts Archival Research Center, 2022)
Small Comforts is an interactive body of work that investigates the sacredness of intimacy, rest, and self-soothing practices. A response to bodily and emotional pain, the sculptures’ softness and tactility invite participants to engage in moments of physical touch. As a prompt to break from the ephemeral and frenetic nature of digital landscapes, Small Comforts asks participants to pause and experience their bodies and minds. Of varied fabrics, shapes, and weights, each sculpture provides an opportunity to explore both the object and the self, alternatingly creating quiet moments of intimacy and groundedness as well as instigating childlike joy at their material and formal silliness. By centering touch, Small Comforts offers an avenue to create and carry embodied states of curiosity, comfort, presence, and pleasure.; Sizes variable; largest sculpture is approximately 5.5' x 1' x 3'; Materials: Satin, cotton, thread, rice, Poly-Fil; Keywords: Soft sculpture, fiber art, sewing, pillows, comfort, intimacy, bodies, color, pattern